18th AIAA/CEAS Aeroacoustics Conference (33rd AIAA Aeroacoustics Conference) 2012
DOI: 10.2514/6.2012-2101
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Realistic Reynolds Numbers on Slat Noise Simulations

Abstract: The slat noise from the 30P/30N high-lift system has been computed using a computational fluid dynamics code in conjunction with a Ffowcs Williams-Hawkings solver. Varying the Reynolds number from 1.71 to 12.0 million based on the stowed chord resulted in slight changes in the radiated noise. Tonal features in the spectra were robust and evident for all Reynolds numbers and even when a spanwise flow was imposed. The general trends observed in near-field fluctuations were also similar for all the different Reyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Moreover, wind tunnel measurements by Herr et al. (2015) with Reynolds numbers up to 5 million, and Navier–Stokes simulations by Lockard & Choudhari (2012) at real-scale Reynolds numbers show similar series of narrowband low-frequency peaks. Therefore, the relevance of the narrowband peaks to full-scale slat noise remains an open question.…”
Section: Introductionmentioning
confidence: 80%
“…Moreover, wind tunnel measurements by Herr et al. (2015) with Reynolds numbers up to 5 million, and Navier–Stokes simulations by Lockard & Choudhari (2012) at real-scale Reynolds numbers show similar series of narrowband low-frequency peaks. Therefore, the relevance of the narrowband peaks to full-scale slat noise remains an open question.…”
Section: Introductionmentioning
confidence: 80%
“…The rare experiments on swept wing noise, carried out in DNW for the A320 wing [1], did not reveal significant narrowband peaks in the slat noise. Whether this is due to the effect of sweep, larger Reynolds numbers or a feature of the specific geometry remains an open question, despite a number of works on this subject [4][5][6][7][8][9]. This paper experimentally investigates the effect of sweep of a wing with the deployed high lift devices on noise mitigation due to the chevron edge of the slat.…”
Section: Introductionmentioning
confidence: 94%
“…Pott-Pollenske, Delfs & Reichenberger (2013) also reported that the slat noise spectra at Re c = 5 × 10 6 did not contain any narrowband peaks. However, Lockard & Choudhari (2012) and Herr et al (2015) found that narrowband peaks robustly existed in the slat noise spectra at Re c = 1.2 × 10 7 and at Re c = 5 × 10 6 , respectively. Although whether narrowband peaks exist in the slat noise spectra at Re c ∼ 10 7 is an open question, massive benchmark investigations captured narrowband peaks in the slat noise spectra at Re c ∼ 10 6 (Murayama et al 2014;Choudhari & Lockard 2015;Li et al 2017Li et al , 2018aPascioni & Cattafesta 2018a).…”
Section: Introductionmentioning
confidence: 97%